JASTRO/JCS Guidelines for radiotherapy in patients with cardiac implantable electronic devices. (4th December 2020) - Ohno, Toshiki; Soejima, Toshinori; Sekiguchi, Yukio; Hashimoto, Takayuki; Koike, Izumi; Matsubara, Hiroaki; Nakamura, Kazuhiko; Nitta, Kazunori; Takahashi, Shigeo; Tsujino, Kayoko; Wakatsuki, Masaru; Yoden, Eisaku
ABSTRACT: This publication is an English version of the Japanese Society for Radiation Oncology (JASTRO) and The Japanese Circulation Society official guidelines for patients with cardiac implantable electronic devices (CIEDs). Several radiotherapy-associated malfunctions have been reported for CIEDs such as pacemakers and implantable cardioverter-defibrillators. Accordingly, guidelines for radiotherapy in patients with CIEDs have been issued by other countries and societies. In August 2010, JASTRO published the 'Radiotherapy Guidelines for Patients with Pacemakers and Implantable Defibrillators' (hereafter referred to as the former guidelines). Given new findings in this decade, a multidisciplinary working group of radiation oncologists, medical physicists, radiation therapists and cardiologists jointly reviewed and revised the former guidelines.